2002
DOI: 10.1097/00007435-200208000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Comparative Pilot Study of Azithromycin Versus Benzathine Penicillin G for Treatment of Early Syphilis

Abstract: Oral therapy with 2.0 g of azithromycin as a single dose or as two doses 1 week apart is a promising alternative to therapy with benzathine penicillin G for syphilis and should be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 12 publications
2
74
0
3
Order By: Relevance
“…Furthermore, they would not lead to the increases in TPPA titres that characterise reinfections. Since all the cases received stage-appropriate, highly effective therapy under direct supervision that has an extremely low failure rate [29], we assume that relapses were very unlikely.…”
Section: (V) Missed Signs Of Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they would not lead to the increases in TPPA titres that characterise reinfections. Since all the cases received stage-appropriate, highly effective therapy under direct supervision that has an extremely low failure rate [29], we assume that relapses were very unlikely.…”
Section: (V) Missed Signs Of Diseasementioning
confidence: 99%
“…This can be inferred from comparing the incubation period of syphilis, being a mean of 21 days (range: 10-90 days) [1,12] and the time to positivity of an RPR test (ca 50% and 90% positive by three and six weeks post infection, respectively) [29] with the frequency of RPR testing (median: 114 days; 3%, 7% and 28% of tests were performed at 7, 14 and 90 days post infection, respectively). As only 28% of tests were performed within the maximum 90-day incubation period, this suggests that the lead-time bias is unable to explain more than a minority of the 91% of the repeat cases presenting asymptomatically.…”
Section: (V) Missed Signs Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…1 Treatment requires obtaining appropriate levels of penicillin in the CSF to exert an antitreponemicidal effect. 24 Because there have been reports of treatment failures despite appropriate penicillin therapy in primary syphilis, 2,25 it is essential to ensure sufficient declines in titres and normal CSF levels following treatment. Data are limited to guide prognostication.…”
Section: Treatmentmentioning
confidence: 99%
“…The results of two pilot studies suggested that the drug may be effective in preventing syphilis in persons exposed to patients with infectious cases 5 and in treating early syphilis. 6 Expanding on these small pilot studies in the United States, we present the results of a randomized, controlled trial conducted in a developing country to test the hypothesis that the efficacy of a single, 2-g oral dose of azithromycin is equivalent to that of standard treatment with 2.4 MU of penicillin G benzathine for the treatment of early syphilis.…”
mentioning
confidence: 99%